METHODOLOGY FOR THE USE OF ELECTRONIC EDUCATIONAL RESOURCES IN THE ORGANIZATION OF INDEPENDENT EDUCATION OF STUDENTS - Alimnazarov, Olim (Foreign Languages ​​in Uzbekistan (JOURNALFLEDU.COM), 2023)
This article is aimed at developing students’ competencies in ensuring the adequacy of the applied methodology to this process based on the results of improving the methodology of using electronic educational resources in organizing independent training of students of the vocational education system through empirical research. Therefore, the use of electronic educational resources in education seems to be a strategic direction for the formation of students’ competencies. As a result of the development of innovative educational technologies, there is a need to ensure the trends in the development of education at the level of modern requirements and the formation of their competence in the use of electronic educational resources in the processes of organizing independent learning. To date, there are many resources in electronic form in professional educational institutions that train personnel at the stage of initial vocational education corresponding to level 3 of the international classifier, but the competence approach to their use is not sufficiently formed. This is because students have insufficiently formed competence in working with electronic educational resources. To form competencies for working with electronic educational resources, including the Compass 3D engineering program, in the process of organizing independent learning of students and improving the methods of performing independent educational tasks using these educational resources, a training session was organized for students of the Termez vocational school of the Surkhandarya region, the results of which were obtained by empirical research, that is, observations, comparative analysis and analysis using methods of mathematical statistics. To a certain extent, this article will serve to improve the methodology for the formation of competencies for working with electronic educational resources in the process of organizing independent training of vocational school students.
Keywords: adequacy; empirical research; creativity; integration; imitation; competence